Perceived destructive coach leadership behavior in elite team sports - Sigvartsen, K.; Sæther, S. A.; Haugen, T.; Erikstad, M.; Peters, D. M.; Høigaard, R. (International Journal of Sport Psychology, 2026)
There is agreement among athletes, coaches, and sport researchers that leadership is one of the most significant factors when performing and operating in elite sport. There is, however, a lack of understanding of how the behaviors of coaches as leaders could be considered as destructive. The aim of this study was to explore elite sport athletes` perceptions and experiences of destructive coach leadership behavior. Informants in this study were a convenience sample of eight (four female and four males) current or former World Class/international elite athletes in handball and soccer, with an average of 12 years of experience at elite level. Using semi-structured interviews and conducting a reflective thematic analysis we identified three main categories of perceived destructive leadership behavior from the coaches described as: Active Destructive Behaviors; Passive Destructive Behaviors, and Incompetent Coach Behaviors. Recognizing these behaviors is the first step in attempting to eradicate them.